Newborn care practices in a tribal community in tamilnadu: a qualitative study - S., Latha; S., Kamala; S., Srikanth (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal mortality is high in tribal areas. Cultural practices influence the newborn health outcomes in tribal communities. Each tribe has its own unique practices on newborn rearing. Little scientific information is available on the beliefs and practices related to essential newborn care among tribes in Tamilnadu. An understanding of the tribe specific newborn care practices by health workers could facilitate them to provide effective newborn care. Methods: A qualitative study was conducted in Sittilingi tribal area in Dharmapuri district of Tamilnadu during the period August and September 2016. The data was collected by In-Depth interviews of 10 mothers with infants, selected by Snow ball sampling method. Local newborn care beliefs and practices were explored and analysis of their beneficial or harmful effects was carried out. Results: The findings show that beneficial practices like utilizing antenatal services, institutional deliveries, delayed bathing and measures to prevent infection were adopted. Harmful practices being followed included late initiation of breastfeeding, denying colostrum, feeding prelacteals, improper thermal care and application of indigenous substances on umbilical cord stump. Conclusions: In spite of utilization of health services, traditional beliefs still play a crucial role in influencing neonatal care practices in the study area. The findings necessitate a need for accessing the prevalence of cultural practices by quantitative studies. Midwives being a vital source of information should be aware of local cultural practices in their work place, to plan for effective behavior change among the mothers to preserve safe practices and avoid harmful practices.